Promising Mass‐Productive 4‐Inch Commercial SERS Sensor with Particle in Micro‐Nano Porous Ag/Si/Ag Structure Using in Auxiliary Diagnosis of Early Lung Cancer - Gao, Yuanmei; Zhu, Hongyu; Wang, Xiaoxiong; Shen, Rong; Zhou, Xiaoming; Zhao, Xiaofei; Li, Zhen; Zhang, Chao; Lei, Fengcai; Yu, Jing (Small (Weinheim an der Bergstrasse, Germany), 2023)
The construction of commercial surface enhanced Raman scattering (SERS) sensors suitable for clinical applications is a pending problem, which is heavily limited by the low production of high‐performance SERS bases, because they usually require fine or complicated micro/nano structures. To solve this issue, herein, a promising mass‐productive 4‐inch ultrasensitive SERS substrate available for early lung cancer diagnosis is proposed, which is designed with a special architecture of particle in micro‐nano porous structure. Benefitting from the effective cascaded electric field coupling inside the particle‐in‐cavity structure and efficient Knudsen diffusion of molecules within the nanohole, the substrate exhibits remarkable SERS performance for gaseous malignancy biomarker, with the limit of detection is 0.1 ppb and the average relative standard deviation value at different scales (from cm2 to µm2) is ≈16.5%. In practical application, this large‐sized sensor can be further divided into small ones (1 × 1 cm2), and more than 65 chips will be obtained from just one 4‐inch wafer, greatly increasing the output of commercial SERS sensor. Further, a medical breath bag composed of this small chip is designed and studied in detail here, which suggested high‐specificity recognition for lung cancer biomarker in mixed mimetic exhalation tests. To construct a commercial surface enhanced Raman scattering (SERS) sensor suitable for clinical diagnosis of early lung cancer, herein, a promising mass‐productive 4‐inch ultrasensitive SERS substrate with a special architecture of particle in micro‐nano porous structure is proposed and researched in detail, which suggests high‐specificity recognition for lung cancer biomarker in exhalation tests.